Twenty-Eight Cases of Extraocular Sebaceous Carcinoma: A Correlative Clinicopathological and Immunohistochemical Analysis of Extraocular Sebaceous Carcinomas and Benign Sebaceous Gland Tumors. (15th February 2021) - Boecker, Werner; Reusch, Michael; Mielke, Volker; Reusch, Ursula; Hallermann, Christian; Loening, Thomas; Tiemann, Markus; Buchwalow, Igor
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Extraocular sebaceous carcinoma (ESC) is a rare appendiceal skin tumor. In contrast to ocular sebaceous carcinoma, information about the exact cellular architecture of these lesions is scarce and the histogenesis of ESC is unknown. Here, we extend our previous study and investigate 28 extraocular carcinomas in comparison to 54 benign sebaceous tumors and 8 cases of normal sebaceous glands using a broad spectrum of antibodies against p63, several keratins, adipophilin, EMA, Ki67, androgen receptor, and mismatch repair proteins. This observational study demonstrates that p63- and K5/14-positive basaloid cells are key cells in normal sebaceous gland and in all sebaceous tumors and that these basaloid cells give rise to EMA+, adipophilin+ sebocytes, and K5/14+, K7±, K10± ductal structures. Finally, about half of ESC is associated with superficial in situ neoplasia, which provides evidence that at least part of these carcinomas arises from flat superficial in situ carcinoma. In contrast to the normal sebaceous gland, about half of all sebaceous tumors lack keratin K7. MMR protein IHC-profiles role will be discussed.